1998
DOI: 10.1002/(sici)1097-4652(199812)177:3<387::aid-jcp2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine TGF? expression in the regulation of initiation of human colon carcinoma growth

Abstract: Previously, we reported that unaggressive, growth factor-dependent FET human colon carcinoma cells downregulated their transforming growth factor alpha (TGFalpha) expression in a quiescent state (G0/G1) induced by growth factor and nutrient deprivation (Mulder, 1991, Cancer Res., 51:2256-2262). In contrast, highly aggressive, growth factor-independent HCT116 human colon carcinoma cells aberrantly upregulated this autocrine activity in the quiescent state (Mulder, 1991, Cancer Res., 51:2256-2262; Howell et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In addition to overexpression, other mechanisms of constitutive activation have been established. For example, constitutive activation of normal levels of ErbB2 by ligand activation provides a signaling basis for several transformed properties in cancer cells (17,39). Disruption of constitutive activation may accomplish reversion of the malignant phenotype or initiation of cell death.…”
Section: Erbb2/erbb3 Heterodimer Formation and Erbb3 Activation-hetermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to overexpression, other mechanisms of constitutive activation have been established. For example, constitutive activation of normal levels of ErbB2 by ligand activation provides a signaling basis for several transformed properties in cancer cells (17,39). Disruption of constitutive activation may accomplish reversion of the malignant phenotype or initiation of cell death.…”
Section: Erbb2/erbb3 Heterodimer Formation and Erbb3 Activation-hetermentioning
confidence: 99%
“…In patients with colon carcinoma, increased EGFR mRNA in the tumors is associated with a higher rate of liver metastasis (14). Previous work in this laboratory indicated that inappropriate expression of EGFR and its ligand, transforming growth factor-␣, associates with neoplastic transformation and induces malignant progression of human colon carcinoma (15,16) as well as activation of ErbB2 (17).…”
mentioning
confidence: 99%
“…Amphiregulin also strongly induces secretion of the matrix metalloproteinases MMP-9 and MMP-2 in cancer cells (81) and is a potent antiapoptotic factor in non-small cell lung cancer cell lines (63). TGF-␣ is also an autocrine/paracrine growth factor acting primarily in the process of growth initiation by moving cells from the non-cycling state back into the cell cycle (69). Increased transcription of amphiregulin and TGF-␣ may reflect the neoplastic origin of Caco-2 cells.…”
Section: Table II Genes Up-regulated During Infection Of Caco-2 Cellsmentioning
confidence: 99%
“…Both EGF and TGFa are overexpressed in the transformed gastrointestinal tract and are therefore acting as paracrine/autocrine agents during cancer progression (Ziober et al, 1993;Jiang et al, 1998;Messa et al, 1998;Wang et al, 1998;Normanno et al, 2001). In order to specify the role of EGFR activation in cellular invasion, we studied the invasion patterns of kidney and colonic cancer cells in response to its natural agonists including EGF, TGFa and amphiregulin.…”
Section: Invasion Patterns Induced By the Egfr Natural Agonistsmentioning
confidence: 99%